Functional Network Profiles in ARSACS Disclosed by Aptamer-Based Proteomic Technology - Morani, Federica; Doccini, Stefano; Chiorino, Giovanna; Fattori, Fabiana; Galatolo, Daniele; Sciarrillo, Elisa; Gemignani, Federica; Züchner, Stephan; Bertini, Enrico Silvio; Santorelli, Filippo Maria (Frontiers in Neurology, 2021)
Although the genetic basis of autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) has been uncovered, the cellular and molecular mechanisms characterizing this rare neurodegenerative disease are still under investigation, and no cure has yet been developed. In this study, we analyzed proteomics data obtained using the SomaLogic technology, comparing cell lysates from ARSACS patients and from a SACS KO SH-SY5Y neuroblastoma cell model. Single-stranded deoxyoligonucleotides, selected in vitro from large random libraries, bound and quantified molecular targets related to the neuroinflammation signaling pathway and to neuronal development. Changes in protein levels were further analyzed by bioinformatics and network approaches to identify biomarkers of ARSACS and functional pathways impaired in the disease. We identified novel significantly dysregulated biological processes related to neuroinflammation, synaptogenesis and engulfment of cells in patients and in KO cells compared with controls. Among the differential expressed proteins found in this work, we identified several proteins encoded by genes already known to be mutated in other forms of neurodegeneration. This finding suggests that common dysfunctional networks could be therapeutic targets for future investigations.